Pengaruh Profesionalisme, Pelatihan dan Gaya Kepemimpinan Terhadap Kinerja Auditor - Fitri Alisa Daulay; Dewi Zulvia (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to examine Professionalism, Training and Leadership Style on auditor performance. Data collection for this research used a questionnaire. The questionnaire was submitted to the Public Accountant Office in Padang City. This research is included in Quantitative research. The sample is determined by purposive sampling technique. Data analysis used multiple regression using SPSS 22 software. The results of this study indicate that professionalism has a positive effect on auditor performance, training has no effect on auditor performance and leadership style has a positive effect on auditor performance.